Developing a screening tool to recognise social determinants of health in Australian clinical settings - Kathryn Browne-Yung; Toby Freeman; Malcolm Battersby; Doug R McEvoy; Fran Baum (Sax Institute, 2019)
Objective and importance of study: The importance of social determinants for individual health recovery outcomes is well recognised in public health. However, no succinct social health screening (SHS) tool exists that has been developed with information from clinicians and patients. This proof-of-concept study asked health consumer advocates, patients and clinicians about their attitudes towards social determinants of health (SDH) and the usefulness of an SHS tool for collecting these data for use in clinical settings. We then developed a streamlined SHS tool to bring this knowledge to clinicians, and conducted a proof-of-concept trial to check its acceptability with patients and clinicians. Methods: This qualitative study had two stages. Stage 1 involved focus groups with health consumer advocates and interviews with clinicians about the draft SHS tool. Stage 2 involved refining the SHS tool and piloting it with 50 new patients in anxiety disorder and sleep disorder clinics, which often treat patients living in disadvantaged socio-economic conditions. The tool was evaluated by patients and clinicians. The data were analysed using framework analysis. Results: All interviewees were positive about the benefits of addressing SDH in clinical practice to help reduce health inequities. We developed and refined an SHS tool that could be completed by patients ('self-complete'). Conclusion: The response to introducing an SHS tool in clinical settings was positive. Further piloting across diverse clinical settings is required to determine efficacy. This tool promotes public health equity outcomes by improving clinician understanding of individual social circumstances, and has the potential to provide useful epidemiological data on SDH.